2012
DOI: 10.1021/jm300122u
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of an Inhibitor of Glucosylceramide Synthase

Abstract: Targeting glycosphingolipid synthesis has emerged as a novel approach for treating metabolic diseases. 32 (EXEL-0346) represents a new class of glucosylceramide synthase (GCS) inhibitors. This report details the elaboration of hit 8 with the goal of achieving and maintaining maximum GCS inhibition in vivo. 32 inhibited GCS with an IC(50) of 2 nM and achieved maximum hepatic GCS inhibition after four or five daily doses in rodents. Robust improvements in glucose tolerance in DIO mice and ZDF rats were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Targeting GCS, due to its central role in the glycosphingolipid synthesis pathway, has emerged as a novel approach for treating metabolic diseases such as Gaucher, Niemann-Pick, and diabetes. In this context, several GCS inhibitors are in clinical use or under development, including miglustat, PDMP, and EXEL-0346 among others (43)(44)(45). Recently, it has been reported that GCS inhibition improved sorafenib effectiveness in vitro and in vivo in experimental hepatocellular carcinoma, recovering drug sensitivity of sorafenib-resistant tumors in mice (46).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting GCS, due to its central role in the glycosphingolipid synthesis pathway, has emerged as a novel approach for treating metabolic diseases such as Gaucher, Niemann-Pick, and diabetes. In this context, several GCS inhibitors are in clinical use or under development, including miglustat, PDMP, and EXEL-0346 among others (43)(44)(45). Recently, it has been reported that GCS inhibition improved sorafenib effectiveness in vitro and in vivo in experimental hepatocellular carcinoma, recovering drug sensitivity of sorafenib-resistant tumors in mice (46).…”
Section: Discussionmentioning
confidence: 99%
“…In this molecule, the introduction of at rifluoromethoxy substituent into the p-position of the phenyl group conferred af ivefold reduction in CYP3A4 inhibitory potency relative to that of the Ha nalogue. [26] The synthesis of 22 is shown in Scheme2,w ith the final step relying upon the condensation of AA 28 with amine 29. [26] The synthesis was initiated by reacting 4-(trifluoromethoxy)phenylacetonitrile (23)w ith 1,2-dibromoethane through as equence of intermolecular alkylation and intramolecular cyclization, which was performed in the presence of NaH in THF,t og enerate the cyclopropylr ing.…”
Section: General Aspects Of Asymmetric Synthesis Of Tailor-made Aasmentioning
confidence: 99%
“…[26] The synthesis of 22 is shown in Scheme2,w ith the final step relying upon the condensation of AA 28 with amine 29. [26] The synthesis was initiated by reacting 4-(trifluoromethoxy)phenylacetonitrile (23)w ith 1,2-dibromoethane through as equence of intermolecular alkylation and intramolecular cyclization, which was performed in the presence of NaH in THF,t og enerate the cyclopropylr ing. Hydrolysis of the cyano group with NaOH at 120 8Cf or 48 hr esulted in acid 24.…”
Section: General Aspects Of Asymmetric Synthesis Of Tailor-made Aasmentioning
confidence: 99%
“…GZ 161, optimized from a large series of carbamates ( 55 ), was shown to reduce brain glucosylceramide levels, improve brain neuropathology, and extend lifespan in the K14 mouse model of Gaucher disease type 2 ( 56 ). A series of lipophilic dipeptides was optimized to yield analogs with low nanomolar inhibition of glucosylceramide synthase and good stability to metabolism by mouse liver microsomes ( 57,58 ). One compound (EXEL-0346) was able to reduce the levels of glucosylceramide, lactosylceramide, and GM3 in the livers of mice after oral dosing.…”
Section: Newer Inhibitorsmentioning
confidence: 99%